Bird-parasite interactions in tropical forests : an ecological and evolutionary perspective (2018)
"The results of this dissertation are a step forward in the understanding of host-parasite interactions in tropical and temperate areas. Overall, the first chapter indicates that host-species are more important than water-related variables in explaining parasite prevalence across environmental gradients, which offers opportunities to study the factors responsible for parasitic infections and how are parasite communities structured in tropical forest. The second chapter we found that prevalence and lineage diversity of haemosporidians varied significantly over the year, being higher during breeding and migration while decreasing during wintering. We found that Gray-cheeked Thrushes shared few parasite lineages with tropical resident birds and slightly more lineages with other migratory and resident-boreal species. My results indicate that long-distance migratory songbirds may not be important dispersers of blood parasites because there are ecological and evolutionary barriers to the interchange of parasites across vastly separated areas. Finally in the third chapter I found that Santa Marta and New Guinea differed in parasite diversity and degree of host-parasite specialization (both were higher in New Guinea), however, I provide evidence for reciprocal elevational zonation between haemosporidian parasites and closely related species of bird as well as variation in prevalence patterns between bird species replacing each other with elevation in both mountain systems. Although these patterns are consistent with predictions of the hypothesis that parasites limit host geographic ranges, additional work including studies of vector ecology and experiments are necessary to determine whether patterns in fact imply causal relationships. I summary my thesis offers a wide perspective on the ecology and evolution of host-parasite interactions in a variety of systems that includes population and community approaches of the host and parasites."--Tomado del Formato de Documento de Grado.